2018
DOI: 10.1097/jom.0000000000001425
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Employment Needs of People With Chronic Health Conditions in Europe

Abstract: Although diverse, there appear to be some common needs transversal to the working experience of people with chronic health problems. Actions to improve the employability of people with chronic health conditions should be tailored to each welfare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Job satisfaction, social support (especially from supervisor), positive work atmosphere, and autonomy are positively associated with productivity in workers with migraine [ 10 , 33 , [67] , [68] , [69] , [70] ]. Migraine-friendly work environment such as natural lights, noise reduction, scent free areas, access to water and restroom, regular breaks, air quality are positively associated with productivity [ 10 , 68 , 71 ] [ 72 , 73 ]. High quantitative work demands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction, social support (especially from supervisor), positive work atmosphere, and autonomy are positively associated with productivity in workers with migraine [ 10 , 33 , [67] , [68] , [69] , [70] ]. Migraine-friendly work environment such as natural lights, noise reduction, scent free areas, access to water and restroom, regular breaks, air quality are positively associated with productivity [ 10 , 68 , 71 ] [ 72 , 73 ]. High quantitative work demands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Non-conducive work environments for people with migraine (lights, computer use, noise, smell, restricted access to water and restroom, restricted breaks) were associated with decreased productivity. Accordingly, migraine-friendly physical adaptations to the work environment were associated with increased productivity (12,29,39,40). Two cross-sectional studies and one prospective cohort study suggested a negative association between quantitative work demands and productivity (28,32,40).…”
Section: Resultsmentioning
confidence: 99%
“…The study designs included cross-sectional (10 studies), prospective cohort (three studies), and a focus-group (one study). Those studies were conducted in Europe (eight studies), the US (two studies), Burkina Faso (one study), Canada (one study), the UK (one study), and Australia (one study) (12,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Job characteristics that were found to be positively associated with productivity included sense of autonomy, social support especially from the supervisor, and job satisfaction.…”
Section: Job Characteristicsmentioning
confidence: 99%
“…Employment needs were, for the purpose of the project, defined according to the framework of the WHO International Classification of Functioning, Disability and Health (ICF) [ 9 ], as the modifiable environmental and/or personal factors that hinder (barriers) or/and facilitate (facilitators) people with chronic health conditions to participate in the labor force and to perform work activities in a similar way as people without chronic conditions. Quantitative results presented in the paper from Ávila and colleagues [ 10 ] showed that “Raising awareness of what is to live with a chronic health condition in the workplace” was the area perceived as more favorable and, on the contrary, “Giving the company the possibility lo legally terminate the job in case productivity decreases due to chronic condition” was rated as unfavorable/very unfavorable by 75% of participants. The types of employment needs were different across the social welfare systems, but did not vary among the different chronic health conditions groups.…”
Section: Employment and People With Non Communicable Chronic Diseamentioning
confidence: 99%